Accuracy of Colposcopically Guided Diagnostic Methods for the Detection of Cervical Intraepithelial Neoplasia - Müller, K.; Soergel, P.; Hillemanns, P.; Jentschke, M. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Many factors can affect the accuracy of colposcopically guided biopsy, endocervical curettage (ECC) and differential cytology, all of which are standard, minimally invasive procedures used to detect cervical intraepithelial neoplasia. Method: All conizations carried out between 2007 and 2013 in the gynecological department of Hannover Medical School were retrospectively reviewed. The agreement between colposcopic diagnosis and histology was evaluated retrospectively. The analysis included 593 complete datasets out of a total of 717 cases treated. Results: The overall agreement was 85.5 %; the accuracy was significantly higher (p = 0.029) when three biopsy specimens were taken rather than just one. The agreement between diagnosis and histological findings from conization was highest for women < 30 years (90.7 %) and lowest for women > 50 years (72.1 %; p = 0.008). The agreement between preoperative differential cytology and histology results after conization was 86.7 % and improved as patient age increased (p = 0.035). The agreement between ECC findings and the results of conization was only 49.1 % irrespective of patient age, transformation zone or the patientʼs menopausal status. Conclusion: The accuracy of colposcopically guided biopsy appears to increase when three biopsy specimens are taken and is particularly high for younger patients. Differential cytology was also found to be highly accurate and is particularly useful for patients aged more than 50 years. The accuracy of ECC was significantly lower; however ECC can provide important additional information in selected cases.
Keywords: virus infection; cervical cancer; cervical intraepithelial neoplasia (CIN); cervix